Uji Invivo Ekstrak Dunaliella salina pada Pakan Komersil terhadap Gejala Klinis dan Patologi Anatomi Ikan Kerapu Cantang Pascainfeksi Viral Nervous Necrosis (VNN) - Rani Yuwanita; Ating Yuniarti (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
Viral Nervous Necrosis (VNN) is a pathogen that is often found infecting cantang grouper and causing mass mortality of up to 100% in a short time. VNN is caused by a Nodavirus infection that infects the nervous and visual systems of fish. One of the prevention efforts against VNN infection in cantang grouper is to add Dunaliella salina extract which contains -carotene, nephtalene, tetradecane and phenol which acts as antiviral, anti-microbial and anti-inflammatory. The purpose of this study was to examine the potency of D. salina extract against clinical symptoms and anatomical pathology of cantang grouper after VNN infection. D. salina extract with doses of 250, 300, 350 and 400mg/kg of feed was added to commercial pelleted feed of the Stella B2 brand with a protein content of 42%. Feed was given to cantang grouper measuring 7-9 cm for 10 days of maintenance. Furthermore, the fish were challenged using VNN as much as 0.2 ml/head through the injection method. Observations of clinical symptoms and anatomical pathology were observed for 96 hours after infection. Symptoms of clinical pathology of fish infected with VNN appear to be circling, swimming horizontally, inflation of the swim bladder, discoloration of the pectoral fins to reddish, swollen lymph organs, yellowing of the liver and darkening of the body color. The compounds found in the extract of D. salina can be used to increase the immune response and reduce the number of deaths of cantang grouper infected with VNN. The addition of D. salina extract which was higher than other doses could increase the immune system so that its survival (SR) was higher as the dose increased.